Correlation of Abdominal Fat Distribution with Different Types of Diabetes in a Chinese Population - Anhui Zhu; Bin Cui; Haodan Dang; Dan Yao; Haitao Yu; Hongmin Jia; Zhijun Hu; Xiaojin Zhang (Journal of Diabetes Research)
To investigate abdominal fat distribution in Chinese subjects with diabetes and its correlation with different types of diabetes. A total of 176 diabetic subjects were enrolled, 92 with type 1 and 84 with type 2, with a mean age of 27.41 and 49.3 yrs. No subject has history of severe diseases. Multi-slice CT was used to measure total abdominal adipose (TA) and visceral adipose (VA) tissues. Subcutaneous adipose (SA) tissue was obtained by subtracting VA from TA. There were differences between subjects with T1DM and T2DM for TA, VA, SA, VA/SA, body mass index (BMI), triglyceride (TG) and high density lipoprotein, but not total Cholesterol or low density lipoprotein. There were positive correlations between TA, VA, SA, VA/SA and T1DM and T2DM (P<0.05 and r>0.86). In subjects with T1DM, VA was negatively correlated with HDL, positively with BMI and age, and SA was positively correlated with BMI and sex (P<0.05 and r>0.86 for all). In subjects with T2DM, VA was positively correlated to BMI, TG and age, and SA was positively correlated to TG and sex (P<0.05 and r>0.86 for all). Abdominal fat content was positively correlated to diabetes in Chinese, which differs in different types of diabetes.